Respiratory symptoms questionnaire for asthma epidemiology: validity and reproducibility. Issue 3 (March 1993) - Venables, K M; Farrer, N; Sharp, L; Graneek, B J; Newman Taylor, A J
Abstract : BACKGROUND: There is a need for a new respiratory symptoms questionnaire for use in epidemiological research in asthma. METHOD: A questionnaire was designed following a pilot study in 78 subjects. It contains nine questions on symptoms such as wheeze and difficulty with breathing in defined circumstances such as exercise and sleep. It was completed by 211 adults and validated by comparison with a self reported history of asthma and with bronchial hyperresponsiveness to histamine. Its short term reproducibility was measured by three repeat administrations over two weeks. RESULTS: Subjects with asthma (n = 33), particularly those having had an asthma attack in the last year (n = 23), were more likely to report any symptom and to report a greater number of symptoms than those without asthma. The same relationship was found for bronchial hyperresponsiveness and symptoms. Either two or more, or three or more, symptoms appeared to be good indices of self reported asthma and bronchial hyperresponsiveness, or both, with a high sensitivity (65-91%) and specificity (85-96%). Reproducibility was good, with few subjects changing the number of symptoms reported by more than one symptom and none by more than four symptoms. The results compared favourably with those from questions on phlegm production from the MRC questionnaire and were better than those reported for the MRC wheeze questions. CONCLUSIONS: The questionnaire will be useful for epidemiological research on asthma and could form part of a new standardised questionnaire with wide applications.